2000
DOI: 10.1002/1522-726x(200012)51:4<402::aid-ccd6>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of coronary blood flow following primary angioplasty for acute myocardial infarction

Abstract: The aim of this study was to evaluate determinants of coronary blood flow following primary angioplasty (PA) in acute myocardial infarction (AMI). The corrected TIMI (thrombolysis in myocardial infarction) frame count and the TIMI flow grade were used as indexes of coronary blood flow, and its determinants were examined in 115 consecutive AMI patients who underwent PA (pain onset Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the present study, patients with reperfused IRA but a closed myocardium (MB grade 0 and 1) had worse collateral blood flow to the infarcted region. Lee, et al 25) reported that a faster corrected TIMI frame count in IRA after primary angioplasty was associated with higher CFIp. This finding implies that the degree of collateral vessel development is associated with microvascular perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, patients with reperfused IRA but a closed myocardium (MB grade 0 and 1) had worse collateral blood flow to the infarcted region. Lee, et al 25) reported that a faster corrected TIMI frame count in IRA after primary angioplasty was associated with higher CFIp. This finding implies that the degree of collateral vessel development is associated with microvascular perfusion.…”
Section: Discussionmentioning
confidence: 99%